Разложите на множители:а 2x — y+x — yб a+ba+2с+2св 3x+2a-c3x+2aг 3x+3y+ax+yд5a-ca-b-5bе ac-2ad-xc-2dё 4ad-3c2a+3x+6dxж x^3+x+yx^2+1з a^2-ab+ca-bи a^3+

Разложите на множители:

а) 2(x - y)+x - y

б) a+b(a+2с)+2с

в) 3x+2a-c(3x+2a)

г) 3x+3y+a(x+y)

д)5a-c(a-b)-5b

е) ac-2ad-x(c-2d)

ё) 4ad-3c(2a+3x)+6dx

ж) x^3+x+y(x^2+1)

з) a^2-ab+c(a-b)

и) a^3+a^2b+ax+bx

й) a^6+a^5-a^4-a^3

  • Сразу пишу, что получится через равно

    й) =a^5(a+1)-a^3(a+1)=(a^5-a^3)(a+1) 

  • е) =а(с-2d)-x(c-2d)=(a-x)(c-2d)

    б) =b(a+2c)+(a+2c)=(b+1)(a+2c)

    з) =a(a-b)+c(a-b)=(a+c)(a-b)

    ж) =x(x^2+1)+y(x^2+1)=(x+y)(x^2+1)

    д) =5(а-b)-c(a-b)=(5-c)(a-b)

    и) =a^2(a+b)+x(a+b)=(a^2+x)(a+b)

    г) =3(х+у)+а(х+у)=(3+а)(х+у)

    ё) =2d(2a+3x)-3c(2a+3x)=(2d-3c)(2a+3x)

    в) =(3х+2а)-с(3х+2а)=(1-с)(3х+2а)

    а) =2(х-у)+(х-у)= (2+1)(х-у)=3(х-у)